Pulsatile leg tumour. First signs of a hypernephroma - Piñeyro, Alberto; Carriquiry, Luis; Sojo, Enrique; Bonaba, Roberto (Cirugía del Uruguay, 1984)
A case is presented of a pseudoaneurismatic tumour in the leg which was the clinical sign of a hypernephroma. Clinical and morphological characteristics of same are analyzed.